Placebo and nocebo in sports: Potential effects of hypothetical differences in roll resistance on roller ski performance - Blumenstein, B.; Abrahamsen, F. E.; Losnegard, T. (Translational Sports Medicine, 2021)
Although placebo and nocebo effects of ergogenic aids are acknowledged as significant for sports performance, little is known about the effects of sports equipment. Therefore, we examined how athletes` belief about their sports equipment affected roller ski performance in a short time trial. In a cross-over design trial, 21 junior cross-country skiers completed a repeated 45 m indoor double poling protocol followed by post-experimental questionnaires on their subjective rating of the performance. All trials were performed on roller skis with equal roll resistance. For the baseline trial, the skis were marked as "medium resistance." For the experimental trials, skis were marked as "low resistance" (placebo), and "high resistance" (nocebo). The mean speed was not different from the placebo trial to the baseline trial, but slower for the nocebo trial compared to the baseline trial (mean ± 95 CI; -0.7% ± 0.4%, P = .005), with a small effect size (Cohen's d = 0.15). Subjective experience of speed as was significantly different from baseline to experimental outcomes (placebo: P < .001; nocebo: P < .002). In conclusion, our findings reveal that athletes' negative perceptions of their sports equipment may have reduced their performance times. However, future examinations should further explore whether athletes' negative perception of equipment may affect their performance.